Copper ink, conductive film forming method, and RF tag

By using copper ink with 60nm to 110nm median diameter fine copper particles on paper substrates, combined with specific dispersion media and dispersant, printing and photosintering technology, the problem of forming a low-resistance conductive film on paper substrates is solved, and the thickness and Low resistance conductive film, suitable for RF tags, and improves durability.

CN119278240APending Publication Date: 2025-01-07ISHIHARA CHEM CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280096531.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-22
Filing Date
2022-08-23
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

It is difficult to form a conductive film with low resistance on a paper substrate, especially because its low heat resistance makes it difficult to succeed in the sintering process.

Method used

Copper ink containing fine copper particles in median diameter 60 nm to 110 nm, combined with alcohols with multiple hydroxyl groups as dispersion medium and polymer compounds with phosphoric acid groups or salts thereof as dispersant, are formed on paper substrates by printing and photosintering technology. Conductive film.

Benefits of technology

The successful formation of a conductive film with a thickness of 1 to 5 μm and a low volume resistivity ensures that the antenna of the RF tag has low resistance, improves signal strength, and enhances the durability of the conductive film in constant temperature and humidity tests.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119278240A_ABST
    Figure CN119278240A_ABST
Patent Text Reader

Abstract

In the present invention, a low-resistance conductive film is formed on a paper substrate. The copper ink according to the present invention includes fine copper particles, a liquid dispersion medium, and a dispersant that disperses the fine copper particles in the dispersion medium. The fine copper particles are copper particles having a median diameter of 60-110 nm. The concentration of the fine copper particles is 60 wt% or more with respect to the entire copper ink. The dispersion medium contains an alcohol having a plurality of hydroxyl groups. The dispersant is a polymer compound having a phosphate group or a salt thereof. The concentration of the dispersant is 3-6 wt% relative to the weight of copper. The copper ink is optically fired to form a conductive film of the paper substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a copper ink for forming a conductive film, a method for forming a conductive film using the copper ink, and an RF tag having the conductive film. Background Art

[0002] RF tags for RFID (radio frequency identification) have been used for product tagging (see non-patent document 1). RFID is a system that uses electromagnetic coupling to read data from RF tags. It should be noted that the Japanese industrial standard JIS Z0667:2017 "Supply chain applications of RFID-Product tagging" in non-patent document 1 corresponds to the international standard ISO 17367:2013 "Supply chain applications of RFID-Product tagging".

[0003] The RF tag has an antenna, wiring, and an IC chip on a resin film such as PET (polyethylene terephthalate). The antenna and wiring are metal foils such as aluminum and are formed on the resin film. The production of the RF tag has a step of etching the metal foil. Therefore, it is costly to process the waste liquid generated by etching. In addition, there has been a recent demand to reduce plastics. However, when the resin film of the RF tag is replaced with a paper substrate, the metal foil on the paper substrate cannot be etched.

[0004] Therefore, it is considered to use copper ink to print antennas for RF tags on paper substrates. Copper ink contains fine copper particles and forms a conductive film by sintering (see, for example, patent document 1). In order to improve the signal strength of the RF tag, the antenna used for the RF tag needs to have a low resistance. Therefore, in order to use copper ink to manufacture the antenna, it is necessary to form a thick conductive film with a low volume resistivity by sintering the copper ink. However, the paper substrate has low heat resistance, so it is difficult to form a thick conductive film with a low volume resistivity on the paper substrate by sintering.

[0005] In addition, it is difficult to form a conductive film having low resistance not only on a paper substrate but also on a substrate having low heat resistance.

[0006] Citation List

[0007] Patent Literature

[0008] Patent Document 1: Japanese Unexamined Patent Application Publication No. JP 2021-152125 Non-Patent Document

[0009] Non-patent document 1: Japanese Industrial Standard JIS Z 0667:2017 Summary of the invention

[0010] Technical issues

[0011] The present invention solves the above-mentioned problems and aims to form a conductive film having a low resistance on a paper substrate.

[0012] Solution to the problem

[0013] The copper ink of the present invention is an ink for forming a conductive film, which contains fine copper particles, a liquid dispersion medium and a dispersant, wherein the fine copper particles are dispersed in the dispersion medium through the dispersant, and the ink is characterized in that the fine copper particles are copper particles with a median diameter of 60 nm or more and 110 nm or less, and the concentration of the fine copper particles is 60 wt % or more relative to the entire copper ink, the dispersion medium includes an alcohol having multiple hydroxyl groups, and the dispersant is a polymer compound having a phosphate group or a salt thereof, and the concentration of the dispersant is 3 wt % or more and 6 wt % or less relative to the weight of the fine copper particles.

[0014] In the copper ink, the dispersion medium preferably includes an alcohol selected from 2-methyl-2,4-pentanediol and 3-methyl-1,3-butanediol.

[0015] The method for forming a conductive film of the present invention is a method for forming a conductive film on a paper substrate, the method comprising the steps of forming an ink film on the paper substrate using copper ink, forming a coated dry film including fine copper particles on the paper substrate by drying the ink film, and performing photo-sintering on the coated dry film.

[0016] The RF tag of the present invention is an RF tag for RFID, having at least a paper substrate and an antenna on the paper substrate, and is characterized in that the antenna includes a conductive film formed by a method for forming a conductive film.

[0017] Advantageous Effects of the Invention

[0018] According to the copper ink of the present invention, the median diameter of the fine copper particles is 60nm or more, so a thick conductive film can be formed on a paper substrate by photo sintering. The median diameter of the fine copper particles is 110nm or less, so a conductive film with low volume resistivity can be formed on a paper substrate by photo sintering. The concentration of the fine copper particles is 60wt% or more relative to the entire copper ink, so a thick conductive film can be formed. The dispersion medium includes an alcohol having multiple hydroxyl groups, so the viscosity and rheological properties (thixotropy) of the copper ink are suitable for printing on a paper substrate through hydrogen bonds with the surface of the fine copper particles. The concentration of the dispersant is 3wt% or more relative to the weight of copper, so the stability of the copper ink is good. The concentration of the dispersant is 6wt% or less, so a conductive film with low volume resistivity can be formed. The conductive film formed is thick and has a low volume resistivity, so the resistance is low. In addition, the dispersant has a phosphate group and the concentration of the dispersant is 3wt% or more, so phosphorus prevents oxidation of copper and enhances the durability of the conductive film in a constant temperature and humidity test. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 (a), (b) and (c) are cross-sectional structural diagrams showing, in chronological order, the formation of a conductive film using the copper ink according to one embodiment of the present invention. DETAILED DESCRIPTION

[0020] A copper ink according to an embodiment of the present invention is described. The copper ink is used to form a conductive film. The copper ink contains fine copper particles, a liquid dispersion medium and a dispersant. The fine copper particles are dispersed in the dispersion medium by the dispersant.

[0021] The fine copper particles are copper particles whose median diameter (D50) is 60 nm or more and 110 nm or less. The particle diameter of the fine copper particles is extracted from the image of the scanning electron microscope (SEM image), and the median diameter is calculated from the particle diameter distribution thereof. When the particle diameter of the fine copper particles is too small, the conductive film formed cannot be made thicker. When the particle diameter is too large, the volume resistivity of the conductive film becomes high.

[0022] The concentration of fine copper particles is 60wt% or more relative to the entire copper ink. When the concentration of fine copper particles is too low, the conductive film formed becomes thinner. The concentration of fine copper particles is ideally 75wt% or less. When the viscosity of the copper ink is high due to too high a concentration of fine copper particles, the unevenness of the printed ink film is greater than that in the case of low viscosity, and a portion thicker than 5μm is generated on the coated dry film formed by drying the ink film. At the time of photo-sintering, the difference in sintering progress between the surface and the bottom of the thicker portion on the coated dry film is large, and the thicker portion is partially blown off, so that a uniform conductive film cannot be formed.

[0023] The dispersion medium includes an alcohol having a plurality of hydroxyl groups. The outermost surface of the fine copper particles is oxidized by oxygen included in the atmosphere to form a thin surface oxide film including copper oxide. In the copper ink, hydrogen bonds are generated between oxygen atoms of copper oxide in the surface oxide film of the fine copper particles and hydrogen atoms of hydroxyl groups in the alcohol. Therefore, the alcohol having a plurality of hydroxyl groups has excellent fine copper particle dispersibility.

[0024] Examples of alcohols having multiple hydroxyl groups include, but are not limited to, 2-methyl-2,4-pentanediol (hexylene glycol), 3-methyl-1,3-butanediol (isoprene glycol), 1,2-ethanediol (ethylene glycol), propane-1,2-diol (propylene glycol), 1,5-pentanediol, 2,2'-oxydiethanol (diethylene glycol), triethylene glycol, 1,2,3-propanetriol (glycerin), and sorbitol.

[0025] The dispersant is a polymer compound or a salt thereof having a phosphoric acid group. A polymer is a molecule having a high molecular weight and has a structure formed by repeating a unit actually or conceptually obtained from a molecule having a smaller molecular weight multiple times (International Union of Pure and Applied Chemistry (IUPAC)). The surface of the fine copper particles is covered with molecules of the dispersant, so that the fine copper particles are dispersed in the dispersion medium.

[0026] The concentration of the dispersant is 3 wt% or more and 6 wt% or less relative to the weight of copper. When the concentration of the dispersant is too low, the dispersibility of the dispersant becomes insufficient and the stability of the copper ink is not good. When the concentration is too high, the dispersant residue remains in the formed conductive film and the volume resistivity of the conductive film becomes high.

[0027] When the dispersant has a phosphoric acid group and the concentration of the dispersant is 3wt% or more, the durability of the formed conductive film in a constant temperature and humidity test is enhanced. This is a discovery of the inventors of the present application. In the analysis of transmission electron microscope (TEM) images by energy dispersive X-ray spectroscopy, phosphorus is retained around sintered fine copper particles in the formed conductive film. Phosphorus prevents oxidation of copper.

[0028] Will refer to Figure 1 (a) to (c) of the present invention describe a method for forming a conductive film using the copper ink. The method for forming a conductive film is a method for forming a conductive film on a paper substrate. Figure 1 As shown in (a), a copper ink 1 is used to form an ink film 2 on a paper substrate 3. The ink film 2 is formed by a printing method. In the printing method, copper ink is used as ink for printing, and the copper ink is applied to a paper substrate 3 in a predetermined pattern by a printing device to form an ink film 2 having the pattern. In this embodiment, the printing system is flexographic printing. Then, the ink film 2 is dried. Figure 1 As shown in (b), by drying the ink film 2, the fine copper particles remain on the paper substrate 3 to form a coated dry film 4 including fine copper particles on the paper substrate 3. The coated dry film 4 including fine copper particles is irradiated with light to perform photo-sintering on the coated dry film 4. For example, the light source for photo-sintering is a xenon lamp. A laser device can be used as the light source. The surface oxide film of the fine copper particles in the coated dry film 4 is removed by light energy, and the fine copper particles are melted to each other to obtain a block. That is, as Figure 1 As shown in (c), the applied dry film 4 is photo-sintered to form a conductive film 5 on the paper substrate 3. It should be noted that the drying of the ink film 2 and the photo-sintering of the applied dry film 4 can be performed simultaneously by light irradiation.

[0029] That is, the method for forming a conductive film includes a step of forming an ink film 2 on a paper substrate 3 using a copper ink 1, a step of forming a coated dry film 4 including fine copper particles on the paper substrate 3 by drying the ink film 2, and a step of photo-sintering the coated dry film 4.

[0030] For example, when copper ink having fine copper particles with a median diameter of 40 nm (which is a particle diameter smaller than the particle diameter in the present embodiment) is used, a conductive film with a low volume resistivity can be formed; however, the conductive film cannot be thick. This is because, when a coated dry film with a thickness of 2 μm or more is formed using copper ink having fine copper particles with a small particle diameter, cracks are generated in the coated dry film. The reason for the cracks is that when the diameter of the fine copper particles is small, the volume shrinkage rate when the ink film is dried becomes larger, and the path through which the dispersion medium travels as a gas disappears due to being filled with fine copper particles with a small particle diameter. The inventors of the present application conducted many experiments and found that fine copper particles with a median diameter of 60 nm to 110 nm are suitable for forming a conductive film on a paper substrate.

[0031] However, when the particle diameter of the fine copper particles is large, the viscosity of the copper ink decreases. Therefore, wet spreading and dripping of the copper ink occur by flexographic printing. Therefore, it is necessary to increase the viscosity of the copper ink. In general, the viscosity of the ink is increased by additives such as resins or rheology control agents. However, in the case of additives of organic substances, their residues become resistors and increase the volume resistivity of the conductive film, so it is desirable to avoid adding additives to the copper ink. The inventors of the present application have found that by using the interaction of hydrogen bonds between the oxygen atoms of copper oxide in the surface oxide film of the fine copper particles and the hydrogen atoms of multiple hydroxyls in the dispersion medium, a copper ink having a viscosity suitable for printing on a paper substrate can be obtained. When the dispersion medium is a monohydric alcohol, the viscosity of the copper ink is insufficient.

[0032] As described above, according to the copper ink of this embodiment, the median diameter of the fine copper particles is 60nm or more, so a thick conductive film can be formed on a paper substrate by photo sintering. The median diameter of the fine copper particles is 110nm or less, so a conductive film with low volume resistivity can be formed on a paper substrate by photo sintering. The concentration of the fine copper particles is 60wt% or more relative to the entire copper ink, so a thick conductive film can be formed. The dispersion medium includes an alcohol having multiple hydroxyl groups, so the viscosity and rheological properties (thixotropy) of the copper ink are suitable for printing on a paper substrate through hydrogen bonds with the surface of the fine copper particles. The concentration of the dispersant is 3wt% or more relative to the weight of copper, so the stability of the copper ink is good. The concentration of the dispersant is 6wt% or less, so a conductive film with low volume resistivity can be formed. The conductive film formed is thick and has a low volume resistivity, so the resistance is low. In addition, the dispersant has a phosphate group and the concentration of the dispersant is 3wt% or more, so phosphorus prevents oxidation of copper and enhances the durability of the conductive film in a constant temperature and humidity test.

[0033] Using the copper ink of this embodiment, a coated dry film with a thickness of 1 to 5 μm can be formed on a paper substrate, and a conductive film with a thickness of about 1 to 2 μm (0.7 to 1.8 μm) can be formed on a paper substrate. The formed conductive film is thick and has a low volume resistivity, so the conductive film has low resistance.

[0034] This copper ink can be used to make RF tags with paper substrates. Figure 1 (c) describes the RF tag. The RF tag 6 is an RF tag for RFID. The RF tag 6 of this embodiment has at least a paper substrate 3 and an antenna on the paper substrate 3. The antenna includes a conductive film 5 formed by the method for forming a conductive film of this embodiment.

[0035] The RF tag 6 has a paper substrate and is therefore eco-friendly. The antenna for the RF tag 6 includes a conductive film 5 formed by the method for forming a conductive film of the present embodiment. The conductive film is thick and has a low volume resistivity, so the antenna has a low resistance. The RF tag 6 has a low-resistance antenna and can therefore obtain sufficient signal strength.

[0036] It should be noted that the RF tag 6 may be laminated. An example of lamination of RF tags is described in Japanese Industrial Standards (see Non-Patent Document 1).

[0037] A copper ink as an example of the present invention and a copper ink as a comparative example thereof were produced, and an experiment was conducted in which a conductive film was formed on a paper substrate using the copper ink.

[0038] Common experimental conditions will be described. Coated paper (trade name "OK TopKote + EF" ("TOPKOTE" is a registered trademark) manufactured by Oji Paper Co., Ltd.) was used as a paper substrate. A wiring test pattern (a line with a width of 0.6 mm) was printed on the paper substrate by flexographic printing using copper ink. The printed ink film had a thickness of 2 to 5 μm. The ink film was dried to form a coated dry film. The film was irradiated by a flash lamp at 4 J / cm 2 The photo-sintering of the coated dry film is carried out at an energy of . The resistance (wiring resistance) of the formed conductive film (line) is measured by a circuit tester at a measuring length of 37.8 mm. In addition, the cross section of the conductive film (line) is measured by a laser microscope. The volume resistivity and average thickness of the conductive film are calculated based on, for example, the resistance value and the cross section. In flexographic printing, the copper ink is not completely transferred from the printing plate to the paper substrate, but is randomly divided between the printing plate and the paper substrate. Therefore, the cross-sectional form of the conductive film formed is generally not smooth and has unevenness. The average thickness of the conductive film is the thickness obtained by averaging the unevenness, that is, the thickness of the rectangle. The formed conductive film (line) is evaluated using the wiring resistance of the formed conductive film (line).

[0039] The composition range of the copper ink in the example will be described. The particle diameter (median diameter) of the fine copper particles is 60 to 110 nm. The median diameter (D50) is calculated based on the diameter frequency distribution of 100 or more fine copper particles randomly sampled from the SEM image of the copper ink at a magnification of ×30000. , the concentration of the fine copper particles is 60 to 75wt% relative to the entire copper ink (hereinafter, the weight % of the fine copper particles is also the same). The dispersant has a phosphate group. The concentration of the dispersion medium is 3 to 6wt% relative to the weight of copper (hereinafter, the weight % of the dispersant is also the same). The dispersion medium is an alcohol having multiple hydroxyl groups. The amount of the dispersion medium is the remainder in the copper ink.

[0040] The composition of the copper ink was changed, and the conductive film formed by photo sintering (photo fired film) was evaluated. It should be noted that, as described above, the cross section and wiring resistance of the conductive film are actual values, while the average thickness and volume resistivity are calculated values.

[0041] Example 1

[0042] Fine copper particles with a median diameter of 80 nm were used for the copper ink (in Examples 2 to 6 and Comparative Examples 1 and 3, the same particles were used). The concentration of the fine copper particles was 75 wt %. Polymer phosphate (trade name manufactured by BYK-Chemie ) was used as a dispersant. The dispersant was a polymer compound having a phosphoric acid group. The concentration of the dispersant was 4 wt %. 2-Methyl-2,4-pentanediol (diol) was used as a dispersion medium.

[0043] The conductive film formed has no cracks. The average thickness of the conductive film is 1.8 μm. The volume resistivity is 5.2 μΩcm. The cross section is 1100 μm 2 The line width is 600μm. The wiring resistance is 1.8Ω. This wiring resistance is the lowest among the examples.

[0044] Example 2

[0045] In the copper ink, the concentration of fine copper particles was 70 wt %, which was lower than that in Example 1. The concentration of the dispersant was 3 wt %, which was lower than that in Example 1. Other conditions were the same as those in Example 1.

[0046] The formed conductive film had no cracks. The average thickness of the conductive film was 1.3 μm, which was thinner than Example 1. The volume resistivity was 5.1 μΩcm, which was lower than Example 1. The cross section was 800 μm 2 The line width is 600μm. The wiring resistance is 2.4Ω, which is higher than that of Example 1.

[0047] The concentration of fine copper particles is lower than that in Example 1, so the average thickness of the conductive film is thinner and the wiring resistance is higher. The concentration of the dispersant is lower than that in Example 1, so the volume resistivity of the conductive film is lower. The concentration of fine copper particles has a great influence on the wiring resistance.

[0048] Example 3

[0049] The concentration of fine copper particles was 60 wt %, which was further lower than that of Example 2. Other conditions were the same as those of Example 2.

[0050] The conductive film formed had no cracks. The average thickness of the conductive film was 0.7 μm, which was thinner than Example 2. The volume resistivity was 5.1 μΩcm, which was the same as Example 1. The cross section was 420 μm 2 The line width is 600μm. The wiring resistance is 4.6Ω, which is higher than that of Example 2.

[0051] The concentration of fine copper particles is lower than that in Example 2, so the average thickness of the conductive film is thinner and the wiring resistance is higher.

[0052] Example 4

[0053] Polymer phosphate ester (trade name manufactured by BYK-Chemie ) was used as a dispersant. The dispersant was a polymer compound having a phosphoric acid group. The concentration of the dispersant was 4 wt %, which was higher than that of Example 3. Other conditions were the same as those of Example 3.

[0054] The formed conductive film had no cracks. The average thickness of the conductive film was 0.7 μm, the same as in Example 3. The volume resistivity was 5.3 μΩcm, higher than in Example 3. The cross section was 420 μm 2 The line width is 600μm. The wiring resistance is 4.8Ω, which is higher than that of Example 3.

[0055] The concentration of the dispersant is higher than that in Example 3, so the volume resistivity of the conductive film is higher and the wiring resistance is higher.

[0056] Example 5

[0057] Alkyl ammonium salt of a copolymer having an acid group (manufactured by BYK-Chemie under the trade name ) was used as a dispersant. The dispersant was a salt of a polymer compound having a phosphate group. Other conditions were the same as those in Example 4.

[0058] The formed conductive film had no cracks. The average thickness of the conductive film was 0.8 μm, which was thicker than Example 4. The volume resistivity was 5.6 μΩcm, which was higher than Example 4. The cross section was 450 μm 2 The line width is 600 μm. The wiring resistance is 4.7 Ω, which is slightly lower than that of Example 4.

[0059] It was found that a salt of a polymer compound having a phosphoric acid group can be used as a dispersant in the copper ink of the present invention.

[0060] Example 6

[0061] The same dispersant as in Examples 1 to 3 was used. 3-Methyl-1,3-butanediol (diol) was used as a dispersion medium. Other conditions were the same as in Example 5.

[0062] The formed conductive film had no cracks. The average thickness of the conductive film was 0.8 μm, the same as in Example 5. The volume resistivity was 5.4 μΩcm, lower than in Example 5. The cross section was 450 μm 2 The line width is 600 μm. The wiring resistance is 4.5 Ω, which is slightly lower than that of Example 5.

[0063] Similar to Examples 1 to 5, the dispersion medium in Example 6 has a plurality of hydroxyl groups. The dispersion medium in Example 6 has a different carbon skeleton from the dispersion medium in Examples 1 to 5, but can be used for the copper ink of the present invention.

[0064] Example 7

[0065] Fine copper particles with a median diameter of 110 nm (larger than Example 2) were used for the copper ink. The concentration of the dispersant was 4 wt %. Other conditions were the same as Example 2.

[0066] The formed conductive film had no cracks. The average thickness of the conductive film was 1.5 μm, which was thicker than Example 2. The volume resistivity was 7.1 μΩcm, which was higher than Example 2. The cross section was 900 μm 2 The line width is 600μm. The wiring resistance is 3.0Ω, which is higher than that of Example 2.

[0067] The median diameter of the fine copper particles is larger than that in Example 2, so the average thickness of the conductive film is thicker and the volume resistivity of the conductive film is higher.

[0068] Example 8

[0069] The concentration of fine copper particles was 60 wt %, which was lower than that of Example 7. Other conditions were the same as those of Example 7.

[0070] The formed conductive film had no cracks. The average thickness of the conductive film was 1.1 μm, which was thinner than Example 7. The volume resistivity was 6.9 μΩcm, which was lower than Example 2. The cross section was 650 μm 2 The line width is 600μm. The wiring resistance is 4.0Ω, which is higher than that of Example 7.

[0071] The concentration of fine copper particles is lower than that of Example 7, so the average thickness of the conductive film is thinner and the wiring resistance is higher.

[0072] Example 9

[0073] Fine copper particles with a median diameter of 60 nm (smaller than Examples 1 to 8) were used for the copper ink. Fine copper particles with a median diameter of 60 nm were obtained by mixing fine copper particles with a median diameter of 40 nm and fine copper particles with a median diameter of 80 nm in a weight ratio of 1:1. The concentration of the dispersant was 6 wt %, which was higher than that of Example 8. Other conditions were the same as those of Example 8.

[0074] The formed conductive film had no cracks. The average thickness of the conductive film was 0.8 μm, which was thinner than Example 8. The volume resistivity was 5.0 μΩcm, which was lower than Example 8. The cross section was 450 μm 2 The line width is 600μm. The wiring resistance is 4.2Ω, which is higher than that of Example 8.

[0075] The median diameter of the fine copper particles is smaller than that in Examples 1 to 8, and thus the volume resistivity of the conductive film is lower than that in Examples 1 to 8.

[0076] Example 10

[0077] Fine copper particles with a median diameter of 100 nm (smaller than Example 8 (110 nm)) were used for the copper ink. The fine copper particles with a median diameter of 100 nm were obtained by mixing fine copper particles with a median diameter of 40 nm and fine copper particles with a median diameter of 110 nm in a weight ratio of 1:4. Other conditions were the same as those of Example 8.

[0078] The formed conductive film had no cracks. The average thickness of the conductive film was 1.2 μm, slightly thicker than Example 8. The volume resistivity was 6.1 μΩcm, lower than Example 8. The cross section was 450 μm 2 The line width is 600μm. The wiring resistance is 3.3Ω, which is lower than that of Example 8.

[0079] The median diameter of the fine copper particles is smaller than that in Example 8, and thus the volume resistivity of the conductive film is lower than that in Example 8.

[0080] The conductive films (line width 600 μm, length 37.8 mm) formed using the copper ink in Examples 1 to 10 had a resistance of 1.8 Ω to 4.8 Ω, which is a low resistance (less than 10 Ω) suitable for an antenna of an RF tag.

[0081] (Comparative Example 1)

[0082] The concentration of fine copper particles was 40 wt %, which was lower than that of Examples 1 to 10. Other conditions were the same as those of Example 1.

[0083] The conductive film formed had no cracks. The average thickness of the conductive film was 0.3 μm, which was thinner than Examples 1 to 10. The volume resistivity was 5.7 μΩcm. The cross section was 200 μm 2The line width was 600 μm. The wiring resistance was 10.8 Ω, which was higher than that of Examples 1 to 10.

[0084] The concentration of fine copper particles is too low, so the average thickness of the conductive film is thinner and the wiring resistance is higher.

[0085] (Comparative Example 2)

[0086] Fine copper particles with a median diameter of 40 nm (smaller than Examples 1 to 10) were used for the copper ink. Other conditions were the same as Example 3.

[0087] The formed conductive film has cracks. The wiring is broken.

[0088] The median diameter of the fine copper particles is too small, so the conductive film has cracks.

[0089] (Comparative Example 3)

[0090] The concentration of the dispersant was 8 wt % higher than that of Examples 1 to 10. Other conditions were the same as those of Example 3.

[0091] The conductive film formed had no cracks. The average thickness of the conductive film was 0.6 μm. The volume resistivity was 10.1 μΩcm, which was higher than that of Examples 1 to 10. The cross section was 380 μm 2 The line width was 600 μm. The wiring resistance was 10.0 Ω, which was higher than that of Examples 1 to 10.

[0092] The concentration of the dispersant is too high, so the volume resistivity of the conductive film is higher and the wiring resistance is higher.

[0093] (Comparative Example 4)

[0094] Fine copper particles with a median diameter of 150 nm (larger than Examples 1 to 10) were used for the copper ink. Other conditions were the same as Example 3.

[0095] The formed conductive film had no cracks. The average thickness of the conductive film was 1.7 μm. The volume resistivity was 31.7 μΩcm, which was higher than that of Examples 1 to 10. The cross section was 1000 μm 2 The line width was 600 μm. The wiring resistance was 12.0 Ω, which was higher than that of Examples 1 to 10.

[0096] The median diameter of the fine copper particles is too large, so the volume resistivity of the conductive film is higher and the wiring resistance is higher.

[0097] The conductive films (line width 600 μm, length 37.8 mm) formed using the copper ink of Comparative Examples 1 to 4 were broken or had high resistance (10Ω or more), which was not suitable for antennas of RF tags.

[0098] A conductive film (line) was formed on a paper substrate in the same manner as in the above example, and the wiring resistance was measured before and after the constant temperature and humidity test. In the constant temperature and humidity test, the temperature was 85°C, the humidity was 85%, and the holding time was 264 hours.

[0099] Example 11

[0100] The conductive film was formed using the same copper ink as in Example 4. That is, the median diameter of the fine copper particles was 80 nm, the concentration of the fine copper particles was 60 wt %, the dispersant was a polymer phosphate, the concentration of the dispersant was 4 wt %, and the dispersion medium was 2-methyl-2,4-pentanediol. The formed conductive film was subjected to a constant temperature and humidity test.

[0101] The wiring resistance of the conductive film was 4.8Ω before the constant temperature and humidity test. The wiring resistance was 9.6Ω after the constant temperature and humidity test. The resistance increase rate was 200%. Only the surface of the conductive film changed color due to oxidation.

[0102] Example 12

[0103] The concentration of the dispersant was 3 wt %, which was lower than that of Example 11. Other conditions were the same as those of Example 11.

[0104] The wiring resistance of the obtained conductive film was 4.6Ω before the constant temperature and humidity test. The wiring resistance was 11.5Ω after the constant temperature and humidity test. The resistance increase rate was 250%. Only the surface of the conductive film was discolored due to oxidation.

[0105] (Comparative Example 5)

[0106] The concentration of the dispersant was 2 wt %, which was lower than that of Example 12. Other conditions were the same as those of Example 11.

[0107] The wiring resistance of the obtained conductive film was 2.8Ω before the constant temperature and humidity test. The wiring resistance could not be measured after the constant temperature and humidity test. The resistance increase rate was ∞. The conductive film could not withstand the constant temperature and humidity test.

[0108] (Comparative Example 6)

[0109] The concentration of the dispersant was 0.5 wt %, which was lower than that of Comparative Example 5. Other conditions were the same as those of Example 11.

[0110] The wiring resistance of the obtained conductive film was 1.2Ω before the constant temperature and humidity test. The wiring resistance could not be measured after the constant temperature and humidity test. The resistance increase rate was ∞. The conductive film could not withstand the constant temperature and humidity test.

[0111] According to Examples 11 and 12 and Comparative Examples 5 and 6, when the dispersant in the copper ink has a phosphoric acid group and the concentration of the dispersant is a specific value or more (3 wt % or more), the durability of the conductive film is enhanced in the constant temperature and humidity test.

[0112] It should be noted that the present invention is not limited to the configuration of the above-described embodiment, and various modifications may be made without changing the gist of the present invention. For example, copper ink may be printed on a paper substrate in a printing system other than flexographic printing. In addition, the RF tag of the present invention is not limited to supply chain applications of RFID.

[0113] Reference numerals list

[0114] 1 Copper ink

[0115] 2 ink film

[0116] 3Paper substrate

[0117] 4. Coating dry film

[0118] 5. Conductive film

[0119] 6RF tag

Claims

1. A copper ink for forming a conductive film, The invention comprises fine copper particles, a liquid dispersion medium and a dispersant, wherein the fine copper particles are dispersed in the dispersion medium by the dispersant. in, The fine copper particles are copper particles having a median diameter of 60 nm or more and 110 nm or less. The concentration of the fine copper particles is 60 wt % or more relative to the entire copper ink. The dispersion medium includes an alcohol having a plurality of hydroxyl groups, The dispersant is a polymer compound having a phosphate group or a salt thereof, and The concentration of the dispersant is 3 wt % or more and 6 wt % or less relative to the weight of the fine copper particles.

2. The copper ink according to claim 1, wherein: The dispersion medium includes an alcohol selected from 2-methyl-2,4-pentanediol and 3-methyl-1,3-butanediol.

3. A method for forming a conductive film to form a conductive film on a paper substrate, in, The method has: The step of forming an ink film on a paper substrate using the copper ink according to claim 1 or claim 2, a step of forming a coated dry film including fine copper particles on the paper substrate by drying the ink film, and The step of performing photosintering on the coated dried film.

4. An RF tag for RFID, At least having a paper substrate and an antenna on the paper substrate, in, The antenna includes a conductive film formed by the method for forming a conductive film according to claim 3.

Citation Information

Patent Citations

  • Copper particle dispersion, conductive film formation method, and circuit substrate

    CN103918037A

  • Coating liquid for forming electroconductive layer, and method for manufacturing electroconductive layer

    CN107949607A

  • Copper particulate dispersion, conductive film forming method and circuit board

    US20140216798A1